An exact quadratic programming approach based on convex reformulation for seru scheduling problems. (2nd September 2022) - Zhang, Zhe; Song, Xiaoling; Gong, Xue; Yin, Yong; Lev, Benjamin; Zhou, Xiaoyang
Abstract: Motivated by a practical production scheduling problem at a factory, this article studies scheduling problems in seru production system (SPS). Seru is a relatively new‐type production mode originating in Japan and has brought inspiring benefits to production practice. Following the just‐in‐time philosophy of SPS, the objective of seru scheduling problem is to minimize the sum of earliness and tardiness penalties. Two common due date types of job are considered, and the seru scheduling problem is formulated as a 0–1 quadratic programming model with linear constraints that is then reformulated using convex reformulation methods to ensure convexity. Computational experiments are implemented. Experimental results indicate that the proposed exact solution method can obtain approximate optimal solutions efficiently and effectively for seru scheduling problems.